Adverse effects of admission blood alcohol on long-term cognitive function in patients with traumatic brain injury. Issue 2 (February 2015) - Joseph, Bellal; Khalil, Mazhar; Pandit, Viraj; Kulvatunyou, Narong; Zangbar, Bardiya; O'Keeffe, Terence; Asif, Anum; Tang, Andrew; Green, Donald J.; Gries, Lynn; Friese, Randall S.; Rhee, Peter
<x xml:space="preserve">Abstract</x> BACKGROUND Alcohol is known to be protective in patients with traumatic brain injury (TBI); however, its impact on the long-term cognitive function is unknown. We hypothesize that intoxication at the time of injury is associated with adverse long-term cognitive function in patients sustaining TBI. METHODS We performed a 2-year retrospective study of all trauma patients with isolated TBI presenting to our Level I trauma center and discharged to a single rehabilitation facility. Patients with moderate-to-severe TBI (head Abbreviated Injury Scale [AIS] score ≥ 3), measured admission blood alcohol concentration, and measured cognitive function on hospital discharge and rehabilitation center discharge were included. Cognitive function was assessed using Functional Independence Measure (FIM) scores. Delta cognitive FIM was defined as the difference between rehabilitation center discharge and hospital discharge cognitive FIM scores. Multivariate linear regression was performed. RESULTS A total of 64 patients were included. Mean (SD) age was 51.8 (23) years, median head AIS score was 3 (IQR, 3–5), and median Glasgow Coma Scale (GCS) score was 11 (IQR, 3–15). Mean (SD) cognitive FIM score on hospital discharge was 17 (6), and mean (SD) cognitive improvement was 8.6 (4.7). Sixty percent (n = 39) were under the influence of alcohol on admission, and the mean (SD) admission blood alcohol concentration was 132 (102). On multivariate linear regression analysis, admission blood alcohol concentration (β = −0.4; 95% confidence interval, −6.7 to −0.8; p = 0.01) and age (β = −0.13; 95% confidence interval, −0.2 to −0.04; p = 0.04) were negatively associated with improvement in long-term cognitive function. CONCLUSION Alcohol intoxication at the time of injury is associated with lower improvement in long-term cognitive function. Older intoxicated patients are likely to have a lower cognitive improvement. LEVEL OF EVIDENCE Prognostic and epidemiologic study, level III.